The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1158/1055-9965.epi-16-0806
|View full text |Cite
|
Sign up to set email alerts
|

Nut Consumption and Lung Cancer Risk: Results from Two Large Observational Studies

Abstract: Background Epidemiological evidence on the association between nut consumption and lung cancer risk is limited. Methods We investigated this relationship in the Environment And Genetics in Lung cancer Etiology (EAGLE) study, a population-based case-control study, and the National Institutes of Health (NIH) American Association of Retired Persons (AARP) Diet and Health Study, a prospective cohort. We identified 2098 lung cases for EAGLE and 18,533 incident cases in AARP. Diet was assessed by food frequency qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In an accompanying Italian case-control study, nut consumption frequency was also significantly associated with a decreased lung cancer risk [12]. A Hawaiian case-control study found no association between peanut and peanut butter intake and lung cancer risk [14], and another Italian case-control study also observed no effect of nut consumption frequency on lung cancer risk [13].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In an accompanying Italian case-control study, nut consumption frequency was also significantly associated with a decreased lung cancer risk [12]. A Hawaiian case-control study found no association between peanut and peanut butter intake and lung cancer risk [14], and another Italian case-control study also observed no effect of nut consumption frequency on lung cancer risk [13].…”
Section: Discussionmentioning
confidence: 97%
“…A third cohort study, the NIH-AARP, with 18,533 incident lung cancer cases found significant inverse associations between nut consumption frequency and risk of adenocarcinoma, squamous cell carcinoma, and small cell carcinoma in both sexes combined, after controlling for smoking characteristics [12]. They also observed that lighter smokers may benefit most from higher nut consumption, and sensitivity analyses suggested that nut intake might be most protective against small cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations